Dual‐Salt Mg‐Based Batteries with Conversion Cathodes. (5th November 2015) - Zhang, Ye; Xie, Junjie; Han, Yanlin; Li, Chilin
Abstract : Mg batteries as the most typical multivalent batteries are attracting increasing attention because of resource abundance, high volumetric energy density, and smooth plating/stripping of Mg anodes. However, current limitations for the progress of Mg batteries come from the lack of high voltage electrolytes and fast Mg‐insertable structure prototypes. In order to improve their energy or power density, hybrid systems combining Li‐driven cathode reaction with Mg anode process appear to be a potential solution by bypassing the aforementioned limitations. Here, FeS x ( x = 1 or 2) is employed as conversion cathode with 2–4 electron transfers to achieve a maximum energy density close to 400 Wh kg −1, which is comparable with that of Li‐ion batteries but without serious dendrite growth and polysulphide dissolution. In situ formation of solid electrolyte interfaces on both sulfide and Mg electrodes is likely responsible for long‐life cycling and suppression of S‐species passivation at Mg anodes. Without any decoration on the cathode, electrolyte additive, or anode protection, a reversible capacity of more than 200 mAh g −1 is still preserved for Mg/FeS2 after 200 cycles. Abstract : In Mg/Li hybrid battery systems with Mg anodes, FeS x ( x = 1 or 2) is employed as conversion cathodes. With 2–4 electron transfers these systems achieve a maximum energy density close to 400 Wh kg −1 without serious dendrite growth and polysulfide dissolution.